SYNTHESIS, CRYSTAL STRUCTURE ANALYSIS AND CHARACTERIZATION OF MERCURY(II) COMPLEX CONTAINING 2-(AMINOMETHYL)PYRIDINE AND BROMIDE - Shirvan, Sadif A.; Khazali, Fereydoon; Haydari Dezfuli, Sara; Borsalani, Ali (Journal of the Chilean Chemical Society, 2017)
The new complex of [Hg(2-AMPy)2Br]2.HgBr4 (1) was synthesized from the reaction of HgBr2 with 2-(aminomethyl)pyridine (2-AMPy) in methanolic solution. Suitable crystals of 1 for diffraction experiment was obtained by slow evaporation from DMSO. Resulted complex was characterized by IR, elemental analysis, thermal analysis and single crystal X-ray diffraction. In this compound, two five-coordinated mercury centers in the cationic parts have slightly and highly distorted square-based pyramidal geometries by the trigonal-indexes, τ5, of 0.18 and 0.49, respectively. According to four-coordinate geometry index, τ4, of 0.95, anionic part has perfect tetrahedral geometry.